Alloying effect on bright–dark exciton states in ternary monolayer MoxW1–xSe2. (12th July 2017) - Liu, Yanping; Tom, Kyle; Zhang, Xiaowei; Lou, Shuai; Liu, Yin; Yao, Jie
Abstract: Binary transition metal dichalcogenides (TMDCs) in the class MX2 (M = Mo, W; X = S, Se) have been widely investigated for potential applications in optoelectronics and nanoelectronics. Recently, alloy-based monolayers of TMDCs have provided a stable and versatile technique to tune the physical properties and optimize them for potential applications. Here, we present experimental evidence for the existence of an intermediate alloy state between the MoSe2 -like and the WSe2 -like behavior of the neutral exciton ( X 0 ) using temperature-dependent photoluminescence (PL) of the monolayer Mo x W1– x Se2 alloy. The existence of a maximum PL intensity around 120 K can be explained by the competition between the thermally activated bright states and the non-radiative quenching of the bright states. Moreover, we also measured localized exciton ( XB ) PL peak in the alloy and the observed behavior agrees well with a model previously proposed for the 3D case, which indicates the theory also applies to 2D systems. Our results not only shed light on bright–dark states and localized exciton physics of 2D semiconductors, but also offer a new route toward the control of the bright–dark transition and tailoring optical properties of 2D semiconductors through defect engineering.